Correlation of the TIGIT-PVR immune checkpoint axis with clinicopathological features in triple-negative breast cancer - Boissière-Michot, Florence; Chateau, Marie-Christine; Thézenas, Simon; Guiu, Séverine; Bobrie, Angélique; Jacot, William (Frontiers in Immunology, 2022)
Background: T cell immunoreceptor with Ig and ITIM domains (TIGIT) interacts with poliovirus receptor (PVR) to contribute to cancer immune escape. Recently, TIGIT and PVR have been identified as promising immunotherapy targets. Their gene expression is upregulated in many solid tumors, but their protein expression level is not well documented, particularly in triple negative breast cancer (TNBC), the breast cancer subtype that most benefit from immunotherapy. Methods: TIGIT and PVR expression levels were assessed by immunohistochemistry in 243 surgically resected localized TNBC and then their relationship with clinical-pathological features and clinical outcome was analyzed. Results: TIGIT expression was observed in immune cells from the tumor microenvironment, whereas PVR was mainly expressed by tumor cells. High TIGIT expression was significantly associated with age (p=0.010), histological grade (p=0.014), non-lobular histology (p=0.024), adjuvant chemotherapy (p=0.006), and various immune cell populations (tumor infiltrating lymphocytes (TILs), CD3+, CD8+, PD-1+ cells; all p<0.0001), PD-L1+ tumor cells (p<0.0001), and PD-L1+ stromal cells (p=0.003). Infiltration by TIGIT+ cells tended to be higher in non-molecular apocrine tumors (p=0.088). PVR was significantly associated with histological grade (p<0.0001), the basal-like (p=0.003) and non-molecular apocrine phenotypes (p=0.039), high TILs infiltration (p=0.011), CD3+ (p=0.002), CD8+ (p=0.024) T cells, and PD-L1 expression in tumor (p=0.003) and stromal cells (p=0.001). In univariate analysis, only known prognostic factors (age, tumor size, lymph node status, adjuvant chemotherapy, TILs and CD3+ T-cell infiltrate) were significantly associated with relapse-free survival (RFS) and overall survival. High TIGIT and PVR expression levels tended to be associated with longer RFS (p=0.079 and 0.045, respectively). The analysis that included only non-molecular apocrine TNBC revealed longer RFS for tumors that strongly expressed TIGIT or PVR (p=0.025 for TIGIT and 0.032 for PVR). Conclusions: These results indicated that in TNBC, TIGIT+ cells can easily interact with PVR to exert their inhibitory effects. Their wide expression in TNBC and their association with other immune checkpoint components suggest the therapeutic interest of the TIGIT-PVR axis.